The importance of stem cells in the treatment of type 1 diabetes, type 2 diabetes and diabetes complications - Monika Kamińska; Maria Jasiewicz; Magdalena Miernik-Skrzypczak; Aleksandra Spyra; Marta Malicka; Natalia Dąbrowska; Aleksandra Kozioł; Katarzyna Moczyróg (Quality in Sport)
Introduction and Purpose. Diabetes, characterized by hyperglycemia due to impaired insulin production or action, leads to significant complications like diabetic retinopathy (DR) and diabetic foot syndrome (DFS). Current treatments manage symptoms but do not fully address disease progression. Stem cells, with their regenerative potential and immunomodulatory properties, represent a promising avenue for treating diabetes and its complications. This study explores the use of stem cell therapy in managing type 1 and type 2 diabetes, DR, and DFS.